Weight loss practices of college wrestlers - Opplinger, R. A.; Nelson Steen, S. A.; Scott, J. R. (International Journal of Sport Nutrition and Exercise Metabolism, 2003)
Purpose: The purpose of this investigation was to examine the weight management (WM) behaviors of collegiate wrestlers after the implementation of the NCAA's new weight control rules. METHODS: In the fall of 1999, a survey was distributed to 47 college wrestling teams stratified by collegiate division (i.e., I, II, III) and competitive quality. Forty-three teams returned surveys for a total of 741 responses. Comparisons were made using the collegiate division, weight class, and the wrestler's competitive winning percentage. Results: The most weight lost during the season was 5.3 kg +/- 2.8 kg (mean +/- SD) or 6.9% +/- 4.7% of the wrestler's weight; weekly weight lost averaged 2.9 kg +/- 1.3 kg or 4.3% +/- 2.3% of the wrestler's weight; post-season, the average wrestler regained 5.5 kg +/- 3.6 kg or 8.6% +/- 5.4% of their weight. Coaches and fellow wrestlers were the primary influence on weight loss methods; however, 40.2% indicated that the new NCAA rules deterred extreme weight loss behaviors. The primary methods of weight loss reported were gradual dieting (79.4%) and increased exercise (75.2%). However, 54.8% fasted, 27.6% used saunas, and 26.7% used rubber/plastic suits at least once a month. Cathartics and vomiting were seldom used to lose weight, and only 5 met three or more of the criteria for bulimia nervosa. WM behaviors were more extreme among freshmen, lighter weight classes, and Division II wrestlers. Compared to previous surveys of high school wrestlers, this cohort of wrestlers reported more extreme WM behaviors. However, compared to college wrestlers in the 1980s, weight loss behaviors were less extreme. Conclusions: The WM practices of college wrestlers appeared to have improved compared to wrestlers sampled previously. Forty percent of the wrestlers were influenced by the new NCAA rules and curbed their weight loss practices. Education is still needed, as some wrestlers are still engaging in dangerous WM methods.